PHYSICAL INTIMATE PARTNER VIOLENCE AGAINST WOMEN IN TURKEY - Ozgenturk, Ilyas (European Scientific Journal, ESJ, 2015)
The purpose of this study is to research how often women experienced physical intimate partner violence living in urban and rural area according to their settlement location, age groups, education status, working status, prosperity levels, and what kind of physical violence they were exposed to and what kind of injuries they had and what were the main reasons of the physical intimate domestic violence against women, according to these women. The data for this study have been taken from the Research about Domestic Violence against Women in Turkey which was conducted by the Republic of Turkey Prime Ministry General Directorate on the Status of Women in 2008. According to this study, at any stage of life, women in rural areas were more likely to be a victim of intimate physical violence than women in urban areas. Women experiencing physical intimate partner violence have been exposed to mostly simple assault such as throwing something, pushing or shoving, fisting, kicking, dragging and beating. Women were more likely to have minor injuries such as scratches and bruises after physical intimate partner violence, both women living in urban areas and in rural areas. Women point out the Problems with the Man’s Family as the number one reason of physical intimate partner violence.